A positive number
This is because you must add to get from a negative number in order to get to a positive number.
Answer:
Step-by-step explanation:
Let's get all of the terms with the on the right-hand side of the equation, and everything else on the left-hand side of the equation.
To do this, we should add to both sides of the equation to remove the from the left-hand side of the equation:
Finally, to get the by itself, we can divide both sides by :
Answer:
1st - Yes ; 2nd - Yes ; 3rd - Yes ; 4th - No
Step-by-step explanation:
━━━━━━━☆☆━━━━━━━
▹ Answer
<em>q = 16</em>
▹ Step-by-Step Explanation
3(q - 7) = 27
3q - 21 = 27
Add 21 to both sides:
21 + 21 = na
27 + 21 = 48
3q = 48
Divide both sides by 3:
3/3 = q
48/3 = 16
q = 16
Hope this helps!
CloutAnswers ❁
━━━━━━━☆☆━━━━━━━